DIGITAL TRANSFORMATION OF THE JUDICIARY: ETHICAL AND LEGAL IMPLICATIONS OF THE USE OF AI IN THE INDONESIAN CRIMINAL JUSTICE SYSTEM - Catur Yunianto; Karman (ADISAM Publisher, 2026)
This article analyses the digital transformation of the judiciary through the use of Artificial Intelligence (AI) in the Indonesian criminal justice system, with a focus on its ethical and legal implications. This qualitative literature review identifies ethical risks such as algorithmic bias, a lack of transparency (the ‘black box’ problem), the dehumanisation of processes, and threats to human rights such as the presumption of innocence and the right to a fair trial. From a legal perspective, inconsistencies were found between the human-centred Criminal Procedure Code and the logic of AI, particularly regarding the admissibility of digital evidence, legal liability for system errors, and the absence of specific regulations for judicial AI. This study recommends a National AI Ethics Framework, PERMA AI for the judiciary, digital literacy training for legal officials, and periodic independent audits to realise digital justice that is fair, accountable, and humane in accordance with the values of Pancasila.